- Optimization of Posyandu Data Collection using Web Information System and Plan Do Check Act Model: - - audia-adika adika-audia (Universitas Multimedia Nusantara, 2026)
This study aims to optimize Posyandu data management through a Web-Based Information System (WBIS) integrated with the PDCA (Plan–Do–Check–Act) cycle to improve the efficiency and sustainability of Maternal and Child Health (MCH) services. A qualitative descriptive approach combined with a Research and Development (R&D) method was employed. Data were collected through observations, interviews, documentation, and literature review. The system was developed using a client–server architecture with a relational database and evaluated through functional testing and user acceptance testing. The results indicate that the prototype effectively integrates digital registration, health record management, and automated reporting. The PDCA integration supports continuous improvement in planning, data recording, evaluation, and intervention processes. User testing demonstrates that the system is user-friendly, reduces data entry errors, and accelerates reporting compared to manual procedures. Although limited to Posyandu in Nagari Pagaruyung, the study provides practical implications by reducing administrative workload for health volunteers and strengthening data-driven decision-making. The novelty lies in embedding the PDCA cycle into a web-based Posyandu Information System as a socio-technical model for continuous improvement in community health data governance.